Evaluation of Speech Processing Capability in Computer Games to Improve the Process of Learning English Pronunciation: An Action Research - Saba Abbasinia; Kazem Pouralvar (Vesnu Publications, 2020)
Introduction: Computer games are a proper approach for information transfer and education. Childhood is the best time to learn a second language and computer games are an attractive interactive tool for this purpose. The purpose of this study is to investigate the ability of speech processing in computer games to improve the process of English language learning and design a game in this regard. Materials and Methods: This was a library-based study to retrieve English and Persian studies in this field and, on the basis of previous studies, a game was designed for children on android platform in the Unity environment using C # language. The child was able to choose a group of words based on color, object, and so on. The game was able to analyze the child' pronunciation and provide feedback to correct it. Results: 50 popular smartphone-specific commercial language learning applications were comprehensively analyzed and three main characteristics were identified for them:  the programs were designed to teach words independently, were tailored to the learner's least skill, and rarely provided learners with corrective feedback. Conclusion: The proposed software seems to be able to be suggested for correcting English pronunciation of individual words in children aged 8 to 10 years in educational centers and language institutes and even at home.